2014
DOI: 10.16948/zktb.68266
|View full text |Cite
|
Sign up to set email alerts
|

Endometri̇al Örnekleme Sonuçlarimiz :744 Olgunun Anali̇zi̇ (Evaluation of Endometrial Biopsy Results in Our Clinic; Analysis of 744 Cases)

Abstract: Amaç: Kliniğimizde endometrial örnekleme yapı-lan olgularda, endikasyon ile histopatolojik sonuçlar arasındaki ilişkinin araştırılması. Gereç ve Yöntem:Kliniğimize Ocak 2013-Ocak 2014 tarihleri arasında başvuran ve gebelik dışı herhangibir endikasyonla endometrial örnekleme yapılan 744 olgu retrospektif olarak değerlendirildi. Veriler hastanemiz kadın hastalıkları ve doğum kliniği ve patoloji kliniği arşivinden alındı. İstatistiksel analiz için SPSS 13 programı kullanıldı. Bulgular:Olguların ortalama yaşları 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…Routine endometrial sampling is not recommended before hysterectomy for exclusion of endometrial pathology in patients presenting with myoma uteri; however, it is still widely performed by many clinicians [5,11]. In our study, EC was not determined in samples obtained due to myoma uteri, similar to the studies in the literature [6,11].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Routine endometrial sampling is not recommended before hysterectomy for exclusion of endometrial pathology in patients presenting with myoma uteri; however, it is still widely performed by many clinicians [5,11]. In our study, EC was not determined in samples obtained due to myoma uteri, similar to the studies in the literature [6,11].…”
Section: Discussionsupporting
confidence: 76%
“…The endometrial hyperplasia rate was reported as 9%-10% in endometrial samples obtained due to abnormal uterine bleeding in the studies of Kucur et al [6] and Tuncer et al [7]. Endometrial hyperplasia was found in 411 (9.68%) cases in our study.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations